2020
DOI: 10.1002/edm2.183
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular and renal effectiveness of empagliflozin in routine care in East Asia: Results from the EMPRISE East Asia study

Abstract: Aim To evaluate the effectiveness of empagliflozin in clinical practice in East Asia in the Empagliflozin Comparative Effectiveness and Safety (EMPRISE) East Asia study. Materials and methods Data were obtained from the Medical Data Vision database (Japan), National Health Insurance Service database (South Korea) and National Health Insurance database (Taiwan). Patients aged ≥ 18 years with type 2 diabetes initiating empagliflozin or a dipeptidyl peptidase‐4 (DPP‐4) inhibitor were 1:1 propensity score (PS) mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 37 publications
9
42
0
Order By: Relevance
“…Lower risks associated with the use of SGLT2is on the safety outcomes of amputation and hospitalized hypoglycemia, which were not assessed in the previous studies of Asian populations, were also observed. These favorable outcomes with SGLT2i use were consistently observed in subgroups stratified by various patient characteristics, which ensures the robustness of our findings as supportive evidence to the existing literature ( 11 , 14 22 , 30 ) shown in the systematic review to promote the rational use of SGLT2is in a diverse group of real-world Asian patients with T2D.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Lower risks associated with the use of SGLT2is on the safety outcomes of amputation and hospitalized hypoglycemia, which were not assessed in the previous studies of Asian populations, were also observed. These favorable outcomes with SGLT2i use were consistently observed in subgroups stratified by various patient characteristics, which ensures the robustness of our findings as supportive evidence to the existing literature ( 11 , 14 22 , 30 ) shown in the systematic review to promote the rational use of SGLT2is in a diverse group of real-world Asian patients with T2D.…”
Section: Discussionsupporting
confidence: 86%
“…Significant beneficial results were consistently observed across studies, with 14–42% ( 19 , 21 ) and 15–66% ( 11 , 17 ) of risk reductions for HHF and all-cause death associated with the use of SGLT2is versus DPP4is, respectively. A 31–77% reduced risk of ESRD or CKD for the use of SGLT2is versus DPP4is was also reported in these studies ( 14 , 15 , 17 ). However, the results for stroke and MI varied across studies.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…A recent study by Patorno et al using real-world data found T2D patients receiving SGLT2 inhibitors had lower risk of hHF, compared to those receiving DPP4 inhibitors, but the magnitudes of the risk differences varied between patients with established ASCVD (44%) and those without established ASCVD (54%) [ 18 ]. Similar findings came from another study using Asian population data [ 19 ]. However, a major issue with these studies was the lack of statistical examinations to test for effect modification by ASCVD on hHF risk.…”
Section: Introductionsupporting
confidence: 89%
“…In the CVD-Real 2/3 observational study, SGLT2 inhibitors were associated with significantly lower risk of cardiovascular events, major kidney events and mortality compared with other oral glucose-lowering drugs in six countries, including Japan, Singapore, and South Korea in CVD-REAL 2, and in five countries, including Japan and Taiwan in CVD-REAL 3 [79,80]. Similarly, in the EMPRISE East Asia study, empagliflozin was associated with a lower risk of hospitalization for heart failure, all-cause mortality and end-stage renal disease compared with DPP-4 inhibitors in Japan, South Korea, and Taiwan [81].…”
Section: Discussionmentioning
confidence: 92%